2018
DOI: 10.3906/sag-1708-67
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of the relationship between autoantibodies andclinical findings in patients with systemic sclerosis

Abstract: Background/aim: We aimed to investigate the prevalence of anti-RNA polymerase (RNAP) III and other autoantibodies in a group of Turkish patients with systemic sclerosis (SSc) and their relation with clinical features. Materials and methods:The prevalence of anti-RNAP III and other autoantibodies was analyzed in 93 patients with SSc and control groups including 86 patients with systemic lupus erythematosus (SLE) and 65 healthy subjects, respectively. Their relationship with diseases findings was assessed in a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
1
2
Order By: Relevance
“…However, the frequency of autoantibodies may vary by ethnicity, and data on SSc-specific autoantibodies from Turkey are limited to the frequencies of anti-Scl70 and anti-centromere antibodies [26]. In addition, in only one study, the frequency of RNAPIII antibodies was reported as 2.2%, which was lower than our results [27]. The difference in results may be because the previous study was conducted in patients with extensive SSc and long disease duration or because the two studies' antibody analysis methods were different.…”
Section: Discussioncontrasting
confidence: 95%
“…However, the frequency of autoantibodies may vary by ethnicity, and data on SSc-specific autoantibodies from Turkey are limited to the frequencies of anti-Scl70 and anti-centromere antibodies [26]. In addition, in only one study, the frequency of RNAPIII antibodies was reported as 2.2%, which was lower than our results [27]. The difference in results may be because the previous study was conducted in patients with extensive SSc and long disease duration or because the two studies' antibody analysis methods were different.…”
Section: Discussioncontrasting
confidence: 95%
“…However, the frequency of autoantibodies may vary by ethnicity, and data on SSc‐specific autoantibodies from Turkey are limited to the frequencies of anti‐Scl70 and anti‐centromere abs 23 . In addition, in only one study, the frequency of anti‐RNAPIII antibodies was reported as 2.2%, which was lower than our results 24 . The difference in results may be because the previous study was conducted in patients with extensive SSc and long disease duration or because the two studies' antibody analysis methods were different.…”
Section: Discussioncontrasting
confidence: 94%
“… 23 In addition, in only one study, the frequency of anti‐RNAPIII antibodies was reported as 2.2%, which was lower than our results. 24 The difference in results may be because the previous study was conducted in patients with extensive SSc and long disease duration or because the two studies' antibody analysis methods were different.…”
Section: Discussionmentioning
confidence: 99%